IL-17 and TH17 responses to human Helicobacter pylori infection and their association with disease - Staples, Emily (2013)
Helicobacter pylori (Hp) is a major cause of peptic ulcer disease (PUD) and gastric cancer, yet the infection remains asymptomatic in most people. One factor that influences the outcome of Hp infection is the host immune response. Expression of the immune-stimulating cytokine interleukin-17 (IL-17) is increased in the human Hp-infected gastric mucosa, but its cellular source and role in pathology are unclear. In this study dendritic cell cytokine responses to Hp stimulation were studied, and relative IL-12p70 and IL-23 concentrations compared, to assess the potential of Hp to promote differentiation of IL-17-secreting T-helper cells (Th17). The effect of Hp virulence factors on cytokine secretion was assessed and monocyte-derived DC (MoDCs) and CD1c+ myeloid DC (MyDC) responses compared. MoDCs produced high concentrations of IL-12p70 upon Hp stimulation. There was also an~ IL-23 MoDCs response, but this was >10-fold lower than the IL-12p70 response. Both IL-12p70 and IL-23 responses were significantly reduced when Hp isogenic mutants for the virulence factor dupA were used, although the effect on MoDC IL-12p70 and IL-23 secretion was less marked than previously reported for monocytes. MyDCs produced lower concentrations of IL-23 than MoDCs, and no detectable IL-12p70. It is known that Hp infection can have systemic effects, so next peripheral blood mononuclear cells (PBMCs) from 21 Hp+ and 13 uninfected patients were stimulated with Hp or control antigen and Th17 and Th1 cell frequencies analyzed by flow cytometry. A systemic Hp-specific Th17 response was identified with higher Th17 cell frequencies in the Hp+ patients compared to the uninfected controls (2.0-fold, p=0.027). A variable proportion of these cells also secreted IFNgamma (median 33%, n=21), but there was no significant correlation between Th17 and Th1 cell frequencies. Peripheral blood Th1 cells were also increased in Hp+ patients (2.1-fold, p=0.018). No significant difference was found between peripheral blood Th17 and Th1 frequencies in the Hp+ patients. The concentrations of Th17, Th1, Th2 and Treg cytokines in the gastric mucosa of Hp+ patients and uninfected controls were investigated using luminex and real-time PCR. High levels of Il-17 expression in the infected compared to uninfected gastric mucosa were confirmed at both the mRNA and protein level (mRNA: 42.6-fold, p<0.0001; protein 3.5-fold, p<0.0001). Il-17 concentrations correlated with the levels of Il-17F (p=0.80, p<0.0001) and the chemokines CCl20 (p=0.59, p<0.0001) and Il-8 (p=0.49, p=0.0004). Concentrations of the Th17-differentiating cytokines IL-1beta, IL-6, IL-21 and IL-23 were not increased in the Hp+ gastric biopsies, although IL-23 was present at high concentrations in all samples regardless of Hp infection status. IL-17 was present at higher concentrations than IFNgamma (3.9-fold, p<0.0001), IL-4 (3.0-fold, p<0.0001) and IL-10 (6.8-fold, p<0.0001) in Hp+ gastric biopsies. IFNG mRNA was also more highly expressed than IL17 mRNA (3.3-fold, p=0.016). To identify the cellular source of the IL-17 mononuclear cells were extracted from gastric biopsies, stimulated with PMA/ionomycin and analyzed by flow cytometry. Amongst biopsy CD3+ T cells from 10 Hp+ patients, IL-17 was produced mainly by CD4+ Th17 cells (68.5%), although CD8+/l-17+ (24.7%) and CD4-CD8- (18.2%) cells also made a significant contribution. High IL-17 concentrations were associated with increased inflammation (2.4-fold, p=0.024) and neutrophil infiltration (2.4-fold, p=0.031). RORC2 mRNA expression was weakly associated with PUD (p=0.046, 1.4-fold) but, surprisingly, no association was found between the IL-17 response and incidence of PUD or precancerous changes. In conclusion Hp can stimulate DCs to produce IL-23 in vitro, and high levels of this Th17-differentiating cytokine were found in gastric mucosal biopsies. Stimulation with dupA null Hp strains led to reduced IL-12p70 and IL-23 secretion, suggesting a possible mechanism of action for this recently discovered virulence factor. Culturing Hp with MoDCs and MyDCs yielded quite different results, and it remains unknown whether either model closely reflects gastric mucosal DC responses. Hp-specific Th17 responses were identified in the peripheral blood of patients with active Hp infection for the first time. Th17 cells were identified as the main cellular source of IL-17 in the Hp-infected gastric mucosa but there were also significant numbers of CDS+IL-17+ and CD4-CDS-IL-17+ T cells, which have not previously been described in this context. High mucosal concentrations of IL-17 and association of this cytokine with infiltration of immune cells indicate that it is an important component of the human immune response to Hp. However, no association between IL-17 and risk of disease was detected in this study, although RORC2 expression was weakly associated with PUD. The role of I L-17/Th 17 in Hp related disease warrants further investigation.